The Effects Of Dietary Fish Oil Replacement On Growth, Tissue Fatty Acid Composition And Fatty Acid Metabolism Of Red Hybrid Tilapia And Genetically Improved Farmed Nile Tilapia - Teoh, Chaiw Yee (2013)
Three related experiments were carried out to investigate the effects of dietary fish oil replacement in the feeds of farmed tilapia. The first feeding trial was conducted to investigate the effects of four different individual vegetable oils (VOs) with varying fatty acid profile as FO alternatives on the growth performance, fatty acid composition and changes in the fatty acid metabolism of red hybrid tilapia (Oreochromis sp.). Full FO replacement by these VOs did not compromise (P>0.05) fish growth performance. In general, dietary VO influenced fatty acid composition of tilapia fillet and whole-body as well as regulating the overall fatty acid metabolism in tilapia. Δ-5, Δ-6 desaturase activity were high in fish fed the VO diets. n-3 long chain-polyunsaturated fatty acid (LC-PUFA) biosynthetic activities were highest in fish fed the canola oil diet and resulted in a superior eicosapentanoic aicd (EPA) + docosahexaenoic acid (DHA) content than the other VO diets. However, endogenous LC-PUFA synthesis triggered by the VO diets was insufficient to rival the n-3 LC-PUFA content of fish fed the FO diet.